1995
DOI: 10.1002/j.1460-2075.1995.tb07353.x
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisomal and mitochondrial carnitine acetyltransferases of Saccharomyces cerevisiae are encoded by a single gene.

Abstract: Carnitine acetyltransferase (CAT) is present in mitochondria and peroxisomes of oleate‐grown Saccharomyces cerevisiae. Both proteins are encoded by the same gene, YCAT, which encodes a protein with a mitochondrial targeting signal (MTS) at the N‐terminus, and a peroxisomal targeting signal type 1 (PTS‐1) at the C‐terminus. Deletion of both motifs revealed the presence of an additional internal targeting sequence. Import of CAT via this internal signal was shown to be dependent on PAS10, a protein which is requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
149
0
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(157 citation statements)
references
References 33 publications
6
149
0
2
Order By: Relevance
“…An example of this type of signal prioritization is seen for the protein carnitine-acetyltransferase, the Cat2 gene product in S. cerevisiae, which contains signals for both mitochondrial and peroxisomal import. Only when Cat2 is missing the mitochondrial-targeting signal, generated through the use of an alternative initiation codon, is it imported into the peroxisome (26).…”
Section: Discussionmentioning
confidence: 99%
“…An example of this type of signal prioritization is seen for the protein carnitine-acetyltransferase, the Cat2 gene product in S. cerevisiae, which contains signals for both mitochondrial and peroxisomal import. Only when Cat2 is missing the mitochondrial-targeting signal, generated through the use of an alternative initiation codon, is it imported into the peroxisome (26).…”
Section: Discussionmentioning
confidence: 99%
“…Proteins delivered to the peroxisome via the Pex7p receptor possess a PTS2, a bipartite amino acid motif with the consensus sequence R/ K-L/V/I-x 5 -H/Q-L/A (Gietl et al, 1994;Glover et al, 1994b) present in the amino terminus of these proteins. A number of proteins can be imported into peroxisomes independent of a recognizable PTS1 or PTS2 (Elgersma et al, 1995;Klein et al, 2002;Ozimek et al, 2006;Small et al, 1988). Subsequent studies have shown that, although the targeting signal is as yet not characterized, Pex5p mediates the peroxisomal sorting of these proteins (Elgersma et al, 1995;Klein et al, 2002;Ozimek et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…A number of proteins can be imported into peroxisomes independent of a recognizable PTS1 or PTS2 (Elgersma et al, 1995;Klein et al, 2002;Ozimek et al, 2006;Small et al, 1988). Subsequent studies have shown that, although the targeting signal is as yet not characterized, Pex5p mediates the peroxisomal sorting of these proteins (Elgersma et al, 1995;Klein et al, 2002;Ozimek et al, 2006). Finally, some proteins can reach the organelle by association with another subunit or protein that possesses a functional targeting signal, a process referred to as 'piggy backing' (Glover et al, 1994a;McNew & Goodman, 1994;Yang et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Protein variants that encode targeting signals at the opposite ends of the protein probably necessitate the omission of the N-terminal targeting signal to disclose a functional PTS1 (lower panel). Thus, the two protein variants should differ in the absence or presence of the N-terminal targeting signal, which can be achieved by the omission of the N-terminal part of the protein sequence either by alternative translation initiation or leaky ribosome scanning (Elgersma et al, 1995;Wamboldt et al, 2009), next to the abovementioned mechanisms of alternative splicing and alternative transcription initiation (Ast et al, 2013).…”
Section: Dual Targeting and Bilocalization Of Proteinsmentioning
confidence: 99%